Catechins within the Biopolymer Matrix-Design Concepts and Bioactivity Prospects - Zvezdelina Yaneva; Donika Ivanova (MDPI AG, 2020)
Epidemiological studies and clinical investigations proposed that catechins extracts alone may not provide a sufficient level of bioactivities and promising therapeutic effects to achieve health benefits due to a number of constraints related to poor oral absorption, limited bioavailability, sensitivity to oxidation, etc. Modern scientific studies have reported numerous techniques for the design of micro- and nano-bio-delivery systems as novel and promising strategies to overcome these obstacles and to enhance catechins' therapeutic activity. The objective assessment of their benefits, however, requires a critical comparative estimation of the advantages and disadvantages of the designed catechins-biocarrier systems, their biological activities and safety administration aspects. In this respect, the present review objectively outlines, compares and assesses the recent advances related to newly developed design concepts of catechins' encapsulation into various biopolymer carriers and their release behaviour, with a special emphasis on the specific physiological biofunctionalities of the innovative bioflavonoid/biopolymer delivery systems.